INTERACT Reducing CO2 Emissions of Arctic Science - Holste, Svenja; Rasch, Morten; Topp-Jørgensen, Elmer (Zenodo, 2022)
The polar scientific community is engaged in various types of fieldwork, conferences, education, training and collaborations, which all come with a significant carbon footprint Many are concerned about Climate Change and its impact on the environment In the Arctic. temperatures are increasing three times faster than in the rest of the world (AMAP, 2021) and the impact of Climate Change is clearly visible. While many environmental impacts are systemic and thus beyond the control of the individual, there are numerous opportunities to reduce C02 emissions that are within the capacity of both institutions and researchers alike. This handbook attempts both to summarize existing knowledge and to offer solutions for researchers who want to reduce C02 emissions related to their research activities. One of the most significant areas under individual control is travel, which is the main focus of the forthcoming chapters.